До можливостей оцiнювання зволоженостi земного покриття за багатоспектральними космiчними зображеннями оптичного дiапазону на прикладi територiї України - Сахацький, О.І.; Станкевич, С.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The paper presents a background and an algorithm for the determination of parameters of land cover moisture using multispectral optical satellite images data. The experimental evaluation of land cover moisture within the territory of Ukraine using MODIS data (resolution of 500 m) for dry and wet season periods has been done. The results of evaluations are well correlated (coeficient of determination r2 6 0.72) with remote sensing evaluation of soil moisture and the vegetation water content by a satellite microwave radiometer AMSR-E. The proposed approach will be useful for the solution of problems concerning the agricultural and natural resources and the environment protection.